2020
DOI: 10.1002/ange.202006384
|View full text |Cite
|
Sign up to set email alerts
|

Cut and Paste for Cancer Treatment: A DNA Nanodevice that Cuts Out an RNA Marker Sequence to Activate a Therapeutic Function

Abstract: DNA nanotechnology uses oligonucleotide strands to assemble molecular structures capable of performing useful operations. Here, we assembled a multifunctional prototype DNA nanodevice, DOCTR, that recognizes a single nucleotide mutation in a cancer marker RNA. The nanodevice then cuts out a signature sequence and uses it as an activator for a “therapeutic” function, namely, the cleavage of another RNA sequence. The proposed design is a prototype for a gene therapy DNA machine that cleaves a housekeeping gene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The DNA machines use several short binding arms rather than one long (15-30 nt) monolith sequences, which is expected to have little or no nonspecific RNA binding when applied in cells. We demonstrated that the cancer maker can be cut out from the longer RNA marker sequence by using two additional Dz agents so that this shorter RNA product can be then used as an activator for cleavage of the targeted RNA 165 . Recently, the binary Dz technology was integrated into a rigid DNA nanostructure named 'Nanotweezer', which was used for cleavage of specific mRNA in living cells 166 , thus proving that this technology can be applied under intracellular conditions.…”
Section: Ribozymes and Deoxyribozymesmentioning
confidence: 99%
“…The DNA machines use several short binding arms rather than one long (15-30 nt) monolith sequences, which is expected to have little or no nonspecific RNA binding when applied in cells. We demonstrated that the cancer maker can be cut out from the longer RNA marker sequence by using two additional Dz agents so that this shorter RNA product can be then used as an activator for cleavage of the targeted RNA 165 . Recently, the binary Dz technology was integrated into a rigid DNA nanostructure named 'Nanotweezer', which was used for cleavage of specific mRNA in living cells 166 , thus proving that this technology can be applied under intracellular conditions.…”
Section: Ribozymes and Deoxyribozymesmentioning
confidence: 99%
“…DNA oligonucleotides (ssDNA) are used as primers and probes in diagnostics, [1] biosensing, [2] and bioanalysis. [3] ssDNA is a material used by DNA nanotechnology for building nanostructures with shapes tailored to specific applications.…”
Section: Introductionmentioning
confidence: 99%